Impact of an Active Learning Methodology on Students' Emotions and Self-Efficacy Beliefs towards the Learning of Chemical Reactions-The Case of Secondary Education Students - Maria Antonia Dávila-Acedo; Jesús Sánchez-Martín; Diego Airado-Rodríguez; Florentina Cañada-Cañada (MDPI AG, 2022)
The main goal of this article was to analyse the impact of the implementation of an active methodology, namely inquiry-based learning, on the emotions experienced by students and their self-efficacy beliefs toward the curricular content in relation to chemical reactions. A sample of 56 students at the third level of compulsory secondary education (K-9) was considered. It was found that the use of an active methodology had on the one hand, a statistically significant effect on the promotion of positive emotions and a decrease in negative emotions and on the other hand a positive effect on the improvement of students' self-efficacy beliefs towards learning the curricular content related to chemical reactions. The implementation of practical activities in the classroom might lead to better learning of scientific content; at least, the results presented in the current article point in that direction.